Early systolic lengthening in patients with ST-elevation myocardial infarction: a novel tool for risk stratification. (4th February 2022) - Ferreira, C; Freitas, A; Martinho, S; Goncalves, V; Almeida, J; Campos, G; Rosa, J; Guimaraes, J; Baptista, R; Castro, G; Goncalves, L
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: After an ST-elevation myocardial infarction (STEMI), the risk of subsequent cardiovascular events is high. Risk stratification at index hospitalization remains a core challenge, especially in patients with subtle changes in LV function. Early systolic lengthening (ESL) may occur in ischemic myocardial segments with reduced contractile force and it has been correlated with infarct size and prognosis in STEMI patients with mildly impaired LV function. In this study, we aimed to evaluate the correlation of ESL with common echocardiographic parameters and its prognostic value in STEMI patients with preserved LV function. Methods: We retrospectively included all the patients admitted to an intensive care unit with STEMI and a left ventricle ejection fraction ≥55% from January to June of 2016. Patients with inadequate image quality for speckle tracking echocardiographic examination were excluded (n = 14). We evaluated the ESL index, defined as follows: [−100×(peak positive systolic strain/peak negative strain in cardiac cycle)], and ESL duration. Results: A total of 37 patients were included in the study. Mean age was 63 ± 12 years with a male preponderance (81%). All patients were submitted to complete revascularization. Median values of the ESL index and ESL duration were 7% (IQR, 4%–10%) and 37 msec (IQR, 21–55 msec), respectively. No significant differences were found between ESL index and ESL duration groups, except for a higher prevalence of heart failure at hospitalization in both highest groups, and women were more prevalent in the ESL index higher group (Tables 1 and 2). ESL index was correlated with post-systolic index (PSI) (r2 = 0.34, p = 0.04) and showed a weak correlation with E/A ratio (r2=-0.37, p = 0.02). ESL duration was correlated with ESL index (r2 = 0.76, p < 0.001) and PSI (r2 = 0.43, p = 0.008). During a median follow‐up of 3.2 years (interquartile range, 2.9–3.4 years), 7 (18.9%) patients experienced major adverse cardiovascular events (MACE), a composite of heart failure admission, myocardial infarction, and all‐cause mortality Both ESL index (HR 2.5; 95%CI 1.2–5.3; P = 0.02) and ESL duration (HR 1.7; 95%CI 1.1–2.7; P = 0.02) were independent predictors of MACE. Both associations remained significant after adjusting for clinical confounders. Conclusions: In our cohort of STEMI patients with preserved LV function, assessment of ESL yielded important and significant prognostic information on MACE. ESL may be a useful tool to enhance routine risk stratification in this population.